Isolation and genomic characteristics of the novel variant infectious bursal disease virus in China - Bo, Zongyi; Wang, Shixu; Xu, Keke; Zhang, Chengcheng; Guo, Mengjiao; Cao, Yongzhong; Zhang, Xiaorong; Wu, Yantao (Frontiers in Veterinary Science, 2023)
The infectious bursal disease virus (IBDV) is a member of the viruses that can induce immunosuppression in chickens. In recent years, more and more IBDV-infected cases by the novel variant IBDV were reported in China, and it has been demonstrated that currently used vaccines could not provide complete protection against these new IBDV variants. However, a lack of comprehensive analysis of the genomic characteristics of the novel variant strain IBDV has hampered its vaccine development. In this study, a strain of IBDV, designated HB202201, was phylogenetically analyzed, and it was found that the hypervariable region (HVR) of VP2 belonged to the novel variant strain.Furthermore, the 5-and 3-ends of segments A and B were analyzed using the rapid amplification of cDNA end (RACE) method. After the full-length of segment A and segment B were determined, the phylogenetic analysis of the segment A and segment B showed that the isolated HB202201 belonged to A2dB1 genotype, which demonstrated the HB202201 belonged to the novel variant strain. In addition, the specific mutations in VP1-VP5 amino acids were analyzed, which showed that there were multiple typical mutations in novel variant IBDV proteins, including VP1 (G24, I141, V163, and E240), VP2 (K221, and I252), VP3 (Q167, and L196), and VP5 (R7, P44, R92, G104, and E147), whereas there was no typical mutation in VP4. This study provides insights into the genomic and antigenic characteristics of the novel variant IBDV, which will promote the development of novel vaccine against the novel variant IBDV.